Effects of aeration, addition of yeast extract and use of spent liquor in the starter culture medium on nata de coco production - Panganiban, Allan Alvin M.; Galvez, Flor Crisanta F. (1995)
The effects of aeration of mother liquor by regular agitation, addition of 0.2% yeast extract, and the use of spent liquor in the preparation of the mother liquor on its microbial flora and yield of the subsequent nata fermentation were studied. Total counts (cfu per milliliter) of Acetobacter xylinum cells, yeast and lactobacillus were determined on Tomoato-Peptone-Sucrose-Salt (TPSS) agar, Malt Yeast Agar (MTA), and De Mann-Rogosa Sharpe (MRS) agar, respectively. Yield and texture of nata de coco produced after fermentation were likewise measured. The aeration method employed and the yeast extract added to the propagation substrate for the culture of mother liquor at the rate used in this study did not have any significant effects on the growth of A. xylinum cells and on the yield and texture of nata produced subsequently from the use of the said mother liquor. Utilization of the spent liquor from previous fermentation as part of the mother liquor significantly decreased the yield of nata and affected the integrity of the pellicle formed but did not affect its texture. This effect was attributed to the presence of considerable amounts of contaminating microorganisms such as the yeasts and lactobacilli in the spent liquor used.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Nata de coco